Investigation of imaging parameters and radiation dose in chest radiographic imaging: A comparison of computed radiography and direct radiography - Sun, Zhonghua; Siddiqui, Salim; Ng, K. (RSNA, 2008)
The aim of the study was to investigate the optimal imaging parameters for chest radiographic imaging using computed radiography (CR) and direct radiography (DR) systems, with regards to the relationship between tube voltage, tube current and radiation dose.